Preparation and Performance of Catalytic Hollow Fibre Membranes for Hydrogenation Reduction of Nitrites in Water - Tong, Gonghe; Song, Jian; Wang, Peng; Zhao, Hongyong; Tan, Xiaoyao (Journal of Membrane and Separation Technology, 2014)
Porous Al2O3 hollow fiber membranes have been fabricated via a phase inversion – sintering technique. Pd-loaded carbon nanotubes (CNTs) are formed inside the hollow fibre wall by the catalytic decomposition of methane over Fe particles, followed by impregnation and reduction with hydrogen to form catalytic hollow fibre membranes. Hydrophobic modification of the hollow fibres is conducted by gas permeable polymeric coating. The resultant hollow fibre membranes exhibit highly catalytic activity to the hydrogenation reduction of nitrites in aqueous solution. Hollow fibre membrane reactors are assembled for nitrite hydrogenation by pumping nitrite solution into the tube side and introducing hydrogen countercurrently to the shell side of the reactor. The nitrite removal in the hollow fibre membrane reactors increases with the operation temperature and the hydrogen feed concentration at lower hydrogen partial pressures, but less influenced by the hydrogen feed concentration when it is higher than 50%. A higher nitrite concentration favors the nitrite hydrogenation reaction but lowers the nitrite removal efficiency.